Effect of radiotherapy for rectal cancer on ovarian androgen production. Issue 3 (12th September 2018) - Segelman, J.; Buchli, C.; Svanström Röjvall, A.; Matthiessen, P.; Arver, S.; Bottai, M.; Ahlberg, M.; Jasuja, R.; Flöter‐Rådestad, A.; Martling, A.
Abstract : Ovarian androgens reduced Abstract : Background: The impact of radiotherapy (RT) for rectal cancer on ovarian androgen production is unknown. The aim was to examine the effect of RT for rectal cancer on androgen levels in non‐oophorectomized women and the association with female sexual desire. Methods: This prospective cohort study included women who had surgery for rectal cancer with or without RT. Serum testosterone, free testosterone, androstenedione and dehydroepiandrosterone sulphate (DHEA‐S) levels were assessed at baseline, after RT and 1 year after surgery. Sexual desire was assessed by means of the Female Sexual Function Index. Results: Twenty‐seven participants had surgery alone (RT– group) and 98 had preoperative RT and surgery (RT+ group). During the first year after surgery, median serum testosterone and free testosterone levels decreased from 0·6 (range 0·1–3·6) to 0·5 (0·1–2·3) nmol/l ( P < 0·001) and from 9·1 (1·6–45·8) to 7·9 (1·4–22·7) pmol/l ( P < 0·001) respectively in the RT+ group, but did not change in the RT– group. Longitudinal regression analysis confirmed a decrease in testosterone and free testosterone after RT. The adjusted change in androstenedione and DHEA‐S was not significant in any group. The mean change in testosterone (odds ratio (OR) 2·74, 95 per cent c.i. 1·06 to 7·11; P = 0·038), free testosterone (OR 1·08, 1·02 to 1·15; P = 0·011), androstenedione (OR 1·52, 1·07 to 2·16; P = 0·019) and DHEA‐S (OR 0·49, 0·27 to 0·89; P = 0·019) was related to change in sexual desire. Conclusion: RT decreased levels of androgens predominantly derived from the ovaries, whereas androgens of mainly adrenal origin remained unchanged. Reduction in ovarian androgens may be associated with reduced sexual desire.